Fluorine-free polyethersulfone and its preparation method and application

By introducing non-coplanar groups and epoxy alkyl groups into the polyether sulfone and using pore-forming agent, the problems of high dielectric constant and poor bonding performance of the polyether sulfone material are solved, and the fluorine-free polyether sulfone is achieved. High heat resistance and good solubility, suitable for microelectronics field.

CN118852625BActive Publication Date: 2025-01-03FUHAI (DONGYING) ADVANCED MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411364447.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

While the existing polyethersulfone materials reduce the dielectric constant, their bonding performance decreases, and release harmful gases at high temperatures, making it difficult to apply in the microelectronics field, and the glass transition temperature decreases, affecting performance.

Method used

By introducing bisphenol compounds with non-coplanar groups and epoxy alkyl groups into the polyethersulfone molecules, combining pore-generating agents, fluoro-free polyethersulfone is prepared, which increases the molecular space volume, hinders the stacking of the main chain, and reduces the dielectric constant. , and maintain high heat resistance and good solubility.

Benefits of technology

It has achieved the significant reduction of the dielectric constant of polyethersulfone while maintaining high heat resistance and good solubility, avoiding the release of harmful gases, and enhancing the environmental friendliness and application value of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The invention discloses fluorine-free polyether sulfone and its preparation method and application, and relates to the technical field of polyether sulfone. The technical scheme is: bisphenol compounds, bisphenol S, 4,4'-dichlorodiphenyl sulfone, acid binding agent, xylene, aprotic polar solvents with non-coplanar groups are mixed, and salt-forming reaction is carried out at 160-170°C under nitrogen protection, and reflux water separation is carried out for 1-3h at the same time, and xylene is steamed out, and the temperature continues to rise to 190-230°C, and the temperature is kept for 4-8h. Sulfolane is added to dilute the polymer solution and cool it to 70-110°C, and epichlorohydrin is added to continue the reaction for 2-10h. After the reaction is completed, the polymer solution is filtered, crushed, washed with an alcohol aqueous solution, and dried to obtain fluorine-free polyether sulfone. The present invention reduces its dielectric constant while keeping polyether sulfone resistant to high heat, and introduces epoxyalkyl groups into the polyether sulfone end group, and the solubility of polyether sulfone in conventional solvents is maintained under the premise of further reducing the dielectric constant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyethersulfone, and in particular to fluorine-free polyethersulfone and a preparation method and application thereof. Background Art

[0002] The rapid development of the field of microelectronics has put forward higher and higher requirements on the dielectric properties of materials. Low dielectric constant and low dielectric loss materials with good comprehensive performance have attracted much attention in recent years. As a type of high-performance thermoplastic engineering plastics, polyethersulfone has high heat resistance, good thermal stability, good chemical resistance and excellent mechanical properties. It is widely used in high-tech fields such as aerospace, national defense, military, and electronics. The dielectric constant of pure polyethersulfone resin is about 3.5. In order to make polyethersulfone materials applicable to low dielectric materials, especially in the field of microelectronics, fluorine-containing components are usually introduced into the molecular structure of polyethersulfone to inhibit the close stacking of material molecules, thereby achieving the purpose of reducing the dielectric constant of polyethersulfone materials. For example, Chinese invention patent CN117384381A discloses a cross-linkable polyarylethersulfone having both high heat resistance and low dielectric constant and a preparation method thereof. 4,4'-dichlorodiphenylsulfone monomer, hexafluorobisphenol A monomer and 2,2'-diallylbisphenol A monomer are synthesized through nucleophilic substitution to obtain a polyarylethersulfone polymer having high heat resistance and low dielectric constant. However, the introduction of a large amount of fluorine-containing components will lead to a decrease in the bonding performance of the material. The hydrofluoric acid released at high temperature is extremely corrosive and has poor environmental friendliness, making it impossible to apply it to the field of precision electronic devices.

[0003] Chinese invention patent CN111205452A discloses a phenolphthalein type high dielectric polyarylether resin containing methylsulfone groups in the side chain and a preparation method thereof, and CN110437446A discloses a polyarylethersulfone containing trifluoropropyl linear organosiloxane and cage silsesquioxane. Cage silsesquioxane and trifluoropropyl linear polyorganosiloxane are introduced into the polyethersulfone structure respectively to synthesize a polyarylethersulfone resin containing a cage silsesquioxane structure, trifluoropropyl linear organosiloxane and cage POSS in the main chain, which effectively reduces the dielectric constant of the polyethersulfone. However, with the introduction of Si-O-Si repeating units and methoxy side groups in the main chain, the glass transition temperature of the polymer decreases to a certain extent.

[0004] Therefore, it is of great significance to design and develop a polyethersulfone with low dielectric constant, high heat resistance and fluorine-free. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art, provide fluorine-free polyethersulfone and its preparation method and application, reduce the dielectric constant of polyethersulfone while maintaining its high heat resistance, and introduce epoxy alkyl groups into the end groups of polyethersulfone to maintain the solubility of polyethersulfone in conventional solvents while further reducing the dielectric constant.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing fluorine-free polyether sulfone, comprising mixing a bisphenol compound having non-coplanar groups, bisphenol S, 4,4'-dichlorodiphenyl sulfone, an acid-binding agent, xylene, and a non-protonic polar solvent, performing a salt-forming reaction at 160-170° C. under nitrogen protection, refluxing and separating water for 1-3 hours, distilling off xylene, continuing to heat to 190-230° C., keeping the temperature for 4-8 hours, adding sulfolane to dilute the polymer solution, cooling the solution to 70-110° C., adding epichlorohydrin to continue the reaction for 2-10 hours, and filtering, crushing, washing with an alcohol aqueous solution, and drying the polymer solution after the reaction is completed to obtain the fluorine-free polyether sulfone; the bisphenol compound having non-coplanar groups and the bisphenol S are mixed and the mixture is stirred for 2 hours. The molar ratio of the total amount of phenol S to 4,4'-dichlorodiphenyl sulfone and the acid binder is 1:(0.85-0.98):(1.05-1.2); the molar ratio of the bisphenol compound with non-coplanar groups to bisphenol S is 1:(4-10); the ratio of the mass of the aprotic polar solvent to the total mass of the bisphenol compound with non-coplanar groups, bisphenol S and 4,4'-dichlorodiphenyl sulfone is (1.2-3):1; the mass ratio of xylene to the aprotic polar solvent is (0.3-0.8):1; the molar ratio of the total amount of the bisphenol compound with non-coplanar groups and bisphenol S to epichlorohydrin is 1:(0.08-0.3).

[0008] Preferably, the bisphenol compound having non-coplanar groups is 4,4'-(2-methylpropylene)bisphenol, 4,4'-(2-pyridylmethyl)bisphenol, 4,4'-(1-phenylethyl)bisphenol, 4,4'-benzhydrylenebisphenol, indan bisphenol or 4,4'-cyclohexylidenebisphenol.

[0009] Among them, the molecular structure of 4,4'-(2-methylpropylene)bisphenol is as follows:

[0010] ;

[0011] The molecular structure of 4,4'-(2-pyridylmethyl)bisphenol is as follows:

[0012] ;

[0013] The molecular structure of 4,4'-(1-phenylethyl)bisphenol is as follows:

[0014] ;

[0015] The molecular structure of 4,4'-diphenylmethylene bisphenol is as follows:

[0016] ;

[0017] The molecular structure of indanyl bisphenol is as follows:

[0018] ;

[0019] The molecular structure of 4,4'-cyclohexylenebisphenol is as follows:

[0020] .

[0021] Preferably, the aprotic polar solvent is sulfolane or diphenyl sulfone.

[0022] Preferably, the acid binding agent is potassium carbonate or sodium carbonate; the alcohol in the alcohol aqueous solution is ethanol or methanol, wherein the volume concentration of the alcohol aqueous solution is ≥30%.

[0023] In a second aspect, the present invention provides fluorine-free polyether sulfone, which is prepared by the above-mentioned preparation method of fluorine-free polyether sulfone.

[0024] In a third aspect, the present invention provides an application of fluorine-free polyethersulfone, wherein the fluorine-free polyethersulfone is dissolved in a polar solvent to obtain a solution with a concentration of 10-20wt.%, and then a porogen is added and stirred until completely dissolved, and the solution is poured onto a glass plate after standing to degas, and then scraped into a liquid film, and the glass plate is immersed in a mixed solution of ethanol and water, and after the liquid film is converted into a solid film, it is peeled off from the glass plate, immersed in deionized water, drained, and vacuum dried to obtain a fluorine-free polyethersulfone membrane; the porogen is polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose or carboxymethyl cellulose.

[0025] Preferably, the polar solvent is N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.

[0026] Preferably, the mass ratio of the porogen to the fluorine-free polyethersulfone is 1:(5-20).

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention uses bisphenol S as the first monomer, 4,4'-dichlorodiphenyl sulfone as the second monomer, and a bisphenol compound with non-coplanar groups as the third monomer to obtain a polyethersulfone copolymer through a one-step reaction; and then obtains a polyethersulfone copolymer with an epoxy group as the terminal group by epoxidation modification of the terminal group of the polyethersulfone copolymer. The present invention introduces a bisphenol compound with non-coplanar groups into the molecular main chain of polyethersulfone to increase the molecular space volume, increase the free volume of the polymer, and hinder the main chain stacking of the polymer, thereby reducing the dielectric constant of polyethersulfone while maintaining high heat resistance; at the same time, an alkylene oxide is introduced into the terminal group of polyethersulfone, and the polyethersulfone is kept in a good solubility at room temperature in solvents such as THF, CHCl3, DMF, DMAC, NMP, DMSO, etc. while further reducing the dielectric constant; in addition, the density of polyethersulfone is adjusted by adding a porogen, so that the dielectric constant of polyethersulfone is further reduced.

[0029] 2. The glass transition temperature Tg of the polyethersulfone prepared by the present invention reaches above 225°C, the 5% thermal weight loss temperature Td5 under N2 is above 529°C, and the dielectric constant at 1MHz is between 2.15-2.73, indicating that the polyethersulfone prepared by the present invention has a low dielectric constant while maintaining high heat resistance.

[0030] 3. The fluorine-free polyethersulfone prepared by the present invention will not release toxic and harmful substances such as fluorophosgene when heated, and has important potential application value in the fields of microelectronics and new energy. DETAILED DESCRIPTION

[0031] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0032] Example 1

[0033] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0034] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 12.115g of 4,4'-(2-methylpropylene)bisphenol, 62.568g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of potassium carbonate, 152g of xylene and 240mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 2h, xylene was evaporated, the temperature was continued to be raised to 210°C and kept warm for 4h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 70°C, 5.551g of epichlorohydrin was added and the reaction was continued for 10h. After the reaction, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain fluorine-free polyether sulfone.

[0035] The molecular structure of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0036] , where m:n=1:5.

[0037] 30 g of the fluorine-free polyethersulfone prepared in this example was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen polyvinylpyrrolidone was added. The solution was mechanically stirred at a speed of 100 r / min for 1 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100° C. to obtain a fluorine-free polyethersulfone membrane.

[0038] Example 2

[0039] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0040] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 8.32g of 4,4'-(2-pyridylmethyl)bisphenol, 68.255g of bisphenol S, 73.226g of 4,4'-dichlorodiphenyl sulfone, 43.536g of potassium carbonate, 146g of xylene and 178mL of cyclopentane were mixed, the temperature was raised to 170°C, the system was refluxed for 3h, xylene was evaporated, the temperature was continued to be raised to 230°C and kept warm for 8h, 150mL of cyclopentane was added to dilute the polymer solution and cooled to 110°C, 4.164g of epichlorohydrin was added and the reaction was continued for 2h. After the reaction, the polymer solution was filtered, crushed, washed 5 times with 50% by volume ethanol aqueous solution, and dried to obtain fluorine-free polyether sulfone.

[0041] The molecular structure of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0042] , where m:n=1:10.

[0043] 30 g of the fluorine-free polyethersulfone prepared in this example was dissolved in 200 mL of N,N-dimethylacetamide to prepare a solution with a concentration of 15 wt.%, and then 6 g of porogen polyvinyl alcohol was added. The solution was mechanically stirred at a speed of 200 r / min for 2 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 2 days, drained, and vacuum dried at 100° C. to obtain a fluorine-free polyethersulfone membrane.

[0044] Example 3

[0045] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0046] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 17.422g of 4,4'-(1-phenylethyl)bisphenol, 60.0648g of bisphenol S, 84.425g of 4,4'-dichlorodiphenyl sulfone, 45.609g of potassium carbonate, 155g of xylene and 155mL of cyclopentane were mixed, the temperature was raised to 160°C, the system was refluxed for 1h, xylene was evaporated, the temperature was continued to be raised to 190°C and kept warm for 6h, 150mL of cyclopentane was added to dilute the polymer solution and cooled to 70°C, 2.221g of epichlorohydrin was added and the reaction was continued for 6h. After the reaction, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain fluorine-free polyether sulfone.

[0047] The molecular structure of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0048] , where m:n=1:4.

[0049] 30 g of the fluorine-free polyethersulfone prepared in this example was dissolved in 200 mL of N,N-dimethylformamide to prepare a solution with a concentration of 15 wt.%, and then 2 g of porogen hydroxymethyl cellulose was added. The solution was mechanically stirred at a speed of 200 r / min for 2 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 1 day, drained, and vacuum dried at 100° C. to obtain a fluorine-free polyethersulfone membrane.

[0050] Example 4

[0051] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0052] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 13.216g of 4,4'-dibenzhydryl bisphenol, 65.696g of bisphenol S, 81.841g of 4,4'-dichlorodiphenyl sulfone, 44.78g of potassium carbonate, 145g of xylene and 382mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 1h, xylene was evaporated, the temperature was continued to be raised to 190°C and kept warm for 8h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 90°C, 5.551g of epichlorohydrin was added and the reaction was continued for 4h. After the reaction was completed, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain fluorine-free polyether sulfone.

[0053] The molecular structure of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0054] , where m:n=1:7.

[0055] 30 g of the fluorine-free polyethersulfone prepared in this example was dissolved in 300 mL of N-methylpyrrolidone to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen carboxymethyl cellulose was added. The solution was mechanically stirred at a speed of 300 r / min for 2 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 2 days, drained, and vacuum dried at 100° C. to obtain a fluorine-free polyethersulfone membrane.

[0056] Example 5

[0057] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0058] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 11.5g of indan bisphenol, 64.355g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 36.567g of sodium carbonate, 245g of xylene and 306.778lg of diphenyl sulfone were mixed, the temperature was raised to 165°C, the system was refluxed for 3h, xylene was evaporated, the temperature was continued to be raised to 230°C and kept warm for 6h, 150mL of cyclopentane was added to dilute the polymer solution and cooled to 90°C, 5.551g of epichlorohydrin was added and the reaction was continued for 6h. After the reaction, the polymer solution was filtered, crushed, washed 5 times with 50% methanol aqueous solution by volume, and dried to obtain fluorine-free polyether sulfone.

[0059] The molecular structure of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0060] , where m:n=1:6.

[0061] 30 g of the fluorine-free polyethersulfone prepared in this example was dissolved in 150 mL of N-methylpyrrolidone to prepare a solution with a concentration of 20 wt.%, and 1.5 g of porogen hydroxymethyl cellulose was added. The solution was mechanically stirred at a speed of 300 r / min for 3 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. A liquid film with a thickness of 100 μm was then scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100° C. to obtain a fluorine-free polyethersulfone membrane.

[0062] Example 6

[0063] The preparation method of the fluorine-free polyether sulfone of the present embodiment is as follows:

[0064] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator and temperature sensor, 13.418g of 4,4'-cyclohexylenebisphenol, 62.568g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of sodium carbonate, 154g of xylene and 244mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 3h, xylene was evaporated, the temperature was continued to be raised to 230°C and kept warm for 6h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 90°C, 5.551g of epichlorohydrin was added and the reaction was continued for 6h. After the reaction, the polymer solution was filtered, crushed, washed 5 times with 50% by volume ethanol aqueous solution, and dried to obtain fluorine-free polyether sulfone.

[0065] The molecular structural formula of the fluorine-free polyethersulfone prepared in this embodiment is as follows:

[0066] , where m:n=1:5.

[0067] 30 g of the fluorine-free polyethersulfone prepared in this embodiment was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen polyvinylpyrrolidone was added. The solution was mechanically stirred at a speed of 300 r / min for 3 h until it was completely dissolved. After standing for degassing, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out with a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a fluorine-free polyethersulfone membrane.

[0068] Comparative Example 1

[0069] Comparative Example 1: Polyethersulfone was prepared by a conventional method, comprising the following steps:

[0070] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator, and temperature sensor, 75.081g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of sodium carbonate, 152.6g of xylene, and 242mL of cyclopentane sulfone were mixed, the temperature was raised to 165°C, the system was refluxed for 2h, xylene was evaporated, the temperature was continued to be raised to 210°C and kept warm for 4h, 120mL of cyclopentane sulfone was added to dilute the polymer solution and cool it, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain polyether sulfone, whose molecular structure is as follows:

[0071] .

[0072] 30 g of the prepared polyethersulfone was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen polyvinyl alcohol was added. The solution was mechanically stirred at a speed of 100 r / min for 1 hour until it was completely dissolved. After standing to degas, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out with a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a polyethersulfone membrane.

[0073] Comparative Example 2

[0074] The preparation method of the polyethersulfone of Comparative Example 2 comprises the following steps:

[0075] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator, and temperature sensor, 12.115g of 4,4'-(2-methylpropylene)bisphenol, 62.568g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of potassium carbonate, 152g of xylene, and 240mL of cyclopentane sulfone were mixed, the temperature was raised to 165°C, the system was refluxed for 2h, xylene was evaporated, the temperature was continued to rise to 210°C and kept warm for 4h, 120mL of cyclopentane sulfone was added to dilute the polymer solution and cool it, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain polyether sulfone, whose molecular structure is as follows:

[0076] , where m:n=1:5.

[0077] 30 g of the prepared polyethersulfone was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen polyvinylpyrrolidone was added. The solution was mechanically stirred at a speed of 100 r / min for 1 hour until it was completely dissolved. After standing to degas, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out with a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a polyethersulfone membrane.

[0078] Comparative Example 3

[0079] The preparation method of the polyethersulfone of Comparative Example 3 comprises the following steps:

[0080] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator, and temperature sensor, 75.081g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of sodium carbonate, 152g of xylene, and 240mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 2h, xylene was evaporated, the temperature was continued to rise to 210°C and kept warm for 4h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 70°C, 5.551g of epichlorohydrin was added and the reaction was continued for 10h. After the reaction was completed, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain polyethersulfone, whose molecular structure is as follows:

[0081] .

[0082] 30 g of the prepared polyethersulfone was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and then 3 g of porogen polyvinylpyrrolidone was added. The solution was mechanically stirred at a speed of 100 r / min for 1 hour until it was completely dissolved. After standing to degas, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out with a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a polyethersulfone membrane.

[0083] Comparative Example 4

[0084] The preparation method of the polyethersulfone of Comparative Example 4 comprises the following steps:

[0085] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator, and temperature sensor, 12.115g of 4,4'-(2-methylpropylene)bisphenol, 62.568g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.756g of potassium carbonate, 152g of xylene, and 240mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 2h, xylene was evaporated, the temperature was continued to rise to 210°C and kept warm for 4h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 70°C, 5.551g of epichlorohydrin was added and the reaction was continued for 10h. After the reaction was completed, the polymer solution was filtered, crushed, washed 5 times with a methanol aqueous solution with a volume concentration of 30%, and dried to obtain polyethersulfone, whose molecular structure is as follows:

[0086] , where m:n=1:5.

[0087] 30 g of the prepared polyethersulfone was dissolved in 300 mL of N,N-dimethylformamide to prepare a solution with a concentration of 10 wt.%, and the solution was mechanically stirred at a speed of 100 r / min for 1 h until it was completely dissolved. After standing to degas, it was poured onto a glass plate, and then a liquid film with a thickness of 100 μm was scraped out using a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, immersed in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a polyethersulfone membrane.

[0088] Comparative Example 5

[0089] The preparation method of the polyethersulfone of Comparative Example 5 comprises the following steps:

[0090] In a 1L reactor equipped with condensation, N2 protection, stirring, water separator, and temperature sensor, 16.812g of hexafluorobisphenol A, 62.568g of bisphenol S, 77.533g of 4,4'-dichlorodiphenyl sulfone, 49.7556g of potassium carbonate, 157g of xylene, and 249mL of cyclopentane were mixed, the temperature was raised to 165°C, the system was refluxed for 3h, xylene was evaporated, the temperature was continued to rise to 230°C and kept warm for 6h, 120mL of cyclopentane was added to dilute the polymer solution and cooled to 100°C, 5.551g of epichlorohydrin was added and the reaction was continued for 6h. After the reaction was completed, the polymer solution was filtered, crushed, washed 5 times with 50% ethanol aqueous solution by volume, and dried to obtain polyethersulfone, whose molecular structure is as follows:

[0091] , where m:n=1:5.

[0092] 30 g of the prepared polyethersulfone was dissolved in 200 mL of N,N-dimethylformamide to prepare a solution with a concentration of 15 wt.%, and then 3 g of porogen polyvinyl alcohol was added. The solution was mechanically stirred at a speed of 300 r / min for 3 h until it was completely dissolved. After standing to degas, it was poured onto a glass plate. Subsequently, a liquid film with a thickness of 100 μm was scraped out with a wet film preparation device. The glass plate was immersed in a mixed solution of ethanol and water with a concentration of 70 wt.%. After the liquid film was converted into a solid film, it was peeled off from the glass plate, soaked in deionized water for 3 days, drained, and vacuum dried at 100°C to obtain a polyethersulfone membrane.

[0093] The thermal properties, electrical properties and solubility in solvents of the polyethersulfone membranes of Examples 1-6 and Comparative Examples 1-5 were tested. The test results are shown in Table 1-2:

[0094] Table 1 Test results of thermal and electrical properties of polyethersulfone membranes of Examples 1-6 and Comparative Examples 1-5

[0095]

[0096] Table 2 Solubility of polyethersulfone membranes of Examples 1-6 and Comparative Examples 1-5 in solvents

[0097]

[0098] In Table 2, “+” represents complete dissolution, “±” represents partial dissolution, and “-” represents insolubility.

[0099] It can be seen from Table 1-2 that the glass transition temperature Tg of the polyethersulfone membrane prepared in the present invention reaches above 225°C, the 5% thermal weight loss temperature Td5 under N2 is above 529°C, the dielectric constant at 1MHz is between 2.15-2.73, and it has good solubility in conventional solvents.

[0100] Comparative Example 1 uses a traditional method to prepare polyethersulfone, with a dielectric constant of 3.6 and poor solubility in CH3Cl and THF; in comparison, when preparing polyethersulfone in Comparative Example 2, a bisphenol compound with a non-coplanar group is introduced to increase the molecular space volume, increase the free volume of the polymer, and hinder the main chain stacking of the polymer, thereby reducing the dielectric constant of polyethersulfone while maintaining high heat resistance. It can be seen that the glass transition temperature of the polyethersulfone prepared in Comparative Example 2 is increased to 240.3°C, and the dielectric constant is reduced by 14.44% compared with Comparative Example 1, that is, the heat resistance is improved to a certain extent while the dielectric constant is reduced, but the solubility of the polyethersulfone in Comparative Example 2 in CH3Cl and THF is not improved. In order to improve the solubility of polyethersulfone, Comparative Example 3 introduces an alkylene oxide. It can be seen from Comparative Example 3 that polyethersulfone can be dissolved in CH3Cl and THF at room temperature, but its glass transition temperature is reduced and the heat resistance is deteriorated. The glass transition temperature and 5% thermal weight loss temperature of the polyethersulfone prepared in Example 1 are higher than those of the polyethersulfone prepared by the traditional method in Comparative Example 1. It can be seen that the introduction of the bisphenol compound with non-coplanar groups just makes up for the disadvantage of poor heat resistance caused by the epoxyalkyl group. In order to further reduce the dielectric constant, the polyethersulfone is made into a polyethersulfone membrane. By comparing Example 1 with Comparative Example 4, it can be seen that after the porogen is added in Example 1, the dielectric constant of the polyethersulfone is further reduced by about 4.5%. This is because the addition of the porogen makes the polyethersulfone have a large number of pores inside, thereby further reducing the dielectric constant of the system.

[0101] The conventional method for reducing the dielectric constant of polyethersulfone is to introduce fluorine-containing groups to reduce the polarizability of the molecule. As can be seen from Table 1, although the dielectric constant of Comparative Example 5 is lower than that of Comparative Example 1, its glass transition temperature and 5% thermal weight loss temperature are both reduced to a certain extent. The polyethersulfones prepared in Examples 1-6 of the present invention can also reduce the dielectric constant while maintaining high heat resistance. At the same time, epoxyalkyl groups are introduced into the polyethersulfone end groups, and the polyethersulfone is kept at room temperature in solvents such as THF, CHCl3, DMF, DMAC, NMP, DMSO, etc. while further reducing the dielectric constant. The polyethersulfone prepared by the present invention does not contain fluorine, and will not release toxic and harmful substances such as fluorophosgene when heated, and has important potential application value in the fields of microelectronics and new energy.

Claims

1. A method for preparing fluorine-free polyethersulfone, characterized in that: A bisphenol compound with non-coplanar groups, bisphenol S, 4,4'-dichlorodiphenyl sulfone, an acid-binding agent, xylene and a non-protonic polar solvent are mixed, and a salt-forming reaction is carried out at 160-170°C under nitrogen protection, and water is separated by reflux for 1-3 hours, and xylene is evaporated, and the temperature is continued to rise to 190-230°C, and the temperature is kept for 4-8 hours, and cyclopentane is added to dilute the polymer solution and cool it to 70-110°C, and epichlorohydrin is added to continue the reaction for 2-10 hours. After the reaction is completed, the polymer solution is filtered, crushed, washed with an alcohol aqueous solution, and dried to obtain a fluorine-free polyether sulfone; the total amount of the bisphenol compound with non-coplanar groups and bisphenol S is equal to that of 4,4'-dichlorodiphenyl sulfone. The molar ratio of 4'-dichlorodiphenyl sulfone and acid binder is 1:(0.85-0.98):(1.05-1.2); the molar ratio of bisphenol compound with non-coplanar groups to bisphenol S is 1:(4-10); the ratio of the mass of non-protonic polar solvent to the total mass of bisphenol compound with non-coplanar groups, bisphenol S and 4,4'-dichlorodiphenyl sulfone is (1.2-3):1; the mass ratio of xylene to non-protonic polar solvent is (0.3-0.8):1; the molar ratio of the total amount of bisphenol compound with non-coplanar groups and bisphenol S to epichlorohydrin is 1:(0.08-0.3).

2. The method for preparing fluorine-free polyether sulfone according to claim 1, characterized in that: The bisphenol compound having non-coplanar groups is 4,4'-(2-methylpropylene)bisphenol, 4,4'-(2-pyridylmethyl)bisphenol, 4,4'-(1-phenylethyl)bisphenol, 4,4'-benzhydrylenebisphenol, indan bisphenol or 4,4'-cyclohexylidenebisphenol.

3. The method for preparing fluorine-free polyethersulfone according to claim 1, characterized in that: The aprotic polar solvent is sulfolane or diphenyl sulfone.

4. The method for preparing fluorine-free polyether sulfone according to claim 1, characterized in that: The acid-binding agent is potassium carbonate or sodium carbonate; the alcohol in the alcohol aqueous solution is ethanol or methanol, wherein the volume concentration of the alcohol aqueous solution is ≥30%.

5. Fluorine-free polyethersulfone, characterized in that The fluorine-free polyether sulfone is prepared by the preparation method according to any one of claims 1 to 4.

6. Application of fluorine-free polyethersulfone, characterized in that: The fluorine-free polyethersulfone as claimed in claim 5 is dissolved in a polar solvent to obtain a solution with a concentration of 10-20wt.%, and then a porogen is added and stirred until completely dissolved, and poured onto a glass plate after standing for degassing, and then scraped into a liquid film, and the glass plate is immersed in a mixed solution of ethanol and water, and after the liquid film is converted into a solid film, it is peeled off from the glass plate, immersed in deionized water, drained, and vacuum dried to obtain a fluorine-free polyethersulfone membrane; the porogen is polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose or carboxymethyl cellulose.

7. The use of fluorine-free polyethersulfone as claimed in claim 6, characterized in that: The polar solvent is N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.

8. The use of fluorine-free polyethersulfone as claimed in claim 6, characterized in that: The mass ratio of the porogen to the fluorine-free polyethersulfone is 1:(5-20).

Citation Information

Patent Citations

  • Poly(aryl ether sulfone) containing trifluoropropyl linear organosiloxane and polyhedral oligomeric silsesquioxane

    CN110437446A

  • Phenolphthalein type high-dielectric polyarylether resin with side chain containing methyl sulfonyl and preparation method thereof

    CN111205452A

  • Crosslinkable polyarylether sulfone with high heat resistance and low dielectric constant and preparation method of crosslinkable polyarylether sulfone

    CN117384381A

  • High-pressure synthesis method of high-light-transmittance polyether sulfone resin narrow in molecular weight distribution

    CN105330839A

  • High-transparent polysulfone resin and preparation method thereof

    CN105330861A